Safety zone for surgical procedures for the prevention of neurovascular injury in minimally invasive total hip arthroplasty - Pak, Hyon-U; Ri, Kang-Chol; Choe, Tae-Hyok; Pak, Chol-Jin; Ri, Won-Jin (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. With the development of minimally invasive surgery (MIS), decreased incision size produces limited visualization leading to an increased risk of adjacent neurovascular structures during the procedure.The aim was to identify the safest zones of surgical procedures for the prevention of major neurovascular structures around the acetabulum. Material and methods. 84 cadaver pelvic specimens with 168 hips were used to analyze the anatomic relationship between the sciatic nerve and the piriformis muscle in the normal Korean population according to sex and height. We performed a qualitative and quantitative analysis of the anatomic relationship between the acetabulum and the sciatic nerve, based on the clockwise direction method, to identify the safety zones of the surgical procedure’s proximity to the acetabulum. Results. The prevalence of type I (normal type) was more than 79% and 88% in males and females, respectively. Distances A, B and E were 7.1±0.78 mm between the 3 and 4 o’clock position, 14.2±0.67 mm between the 8 and 9 o’clock position, 17.0±1.22 mm in the 9 o’clock position, respectively, on the left side, whereas 6.0±0.69 mm between the 8 and 9 o’clock position, 14.8±0.59 mm in the 7 o’clock position, 17.9±1.08 mm in the 3 o’clock position on the right side. The proximity of the retractors to acetabulum should be placed with careful and proper retraction between the 3 and 5 o’clock position on the left side and between the 7 and 9 o’clock position on the right side, in which the placement in the 9 and 3 o’clock position should be cautious on the right and left side, respectively. The cautious use of electrocautery between the 3 and 5 o’clock position on the left side, and between the 7 and 9 o’clock position on the right side, is recommended. However, performing the electrocauterization in the 9 o’clock and 3 o’clock position respectively on the left and right side should be avoided. It is forbidden between the 10 and 12 on the left side and between 12 and 2 o’clock position on the right side. The absolute safety zones for the placement of the transacetabular screw were between 1 and 3, and between the position 5 and the 6 o’clock position on the left side and between the position 9 and 11, and between the 6 and 7 on the right side. Relative safe zones were between 12 and 1, and between the 6 and 7 o’clock position on the left and between the 11 and 12, and between the 5 and 6 o’clock positions on the right side. Screws with a length of <24mm could be safely inserted between the 3 and 5 o’clock position on the left side and between the 7 and 9 o’clock position on the right side. The risk zones were between 7 and 9, and between the 9 and 12 hours on the left side, and between 3 and 5, and between the 12 and 3 o’clock position on the right side. In cases with highly elevated trochanter major, the distances between the acetabulum and adjacent neurovascular structures changed and the risk of the SN increased. Conclusion. These data could be helpful for arthroplasty surgeons in avoiding neurovascular injuries in MIS THA.